PENGARUH MODEL PBL TERHADAP HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 13 PONTIANAK - Susi Anggraini; Hery Kresnadi; Suhardi Marli (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aims to analyze influence the Problem Based Learning model on the learning outcomes of Natural Sciences in class V of Elementary School 13 West Pontianak. This study uses a Quasi Experimental design in the form of Nonequivalent Control Group Design. The population in this study was  all fifth grade students of West Pontianak 13 Primary School. Sampling was using simple random sampling technique, namely V A. Based on the analysis of the data obtained the average results of the experimental class post-test of 68.6 and post-test of the control class of 61.59, obtained tcount of 2.187 and ttable is 2,002, because tcount > ttable, then Ha is accepted. So, it can be concluded that there is an influence of the application of the Problem Based Learning model to the learning outcomes of Natural Sciences in class V of Elementary School 13 West Pontianak. Based on the results of the calculation of the effect size (d) = 0.572 which is classified as medium criteria. This, it can be said that the Problem Based Learning model has a moderate effect on the learning outcomes of Natural Sciences in class V of Elementary School 13 West Pontianak. Keywords: Natural sciences, Learning outcome, Problem Based learning